MODEL DEVELOPMENT AND OPTIMIZATION IN METHANOLYSIS OF RICE BRAN OIL USING NANOCRYSTALLINE K-ZnO CATALYST: BOX BEHNKEN DESIGN - Kabo, Kamaluddeen Suleiman; Bello, Abdu Muhammad; Yalwa, Ibrahim Rilwanu (FUDMA Journal of Sciences, 2023)
In this study, nanocrystalline zinc oxide (ZnO) was precipitated and modified with 2.26% (wt.) potassium (K) through wet impregnation and used for Response Surface Methodology Box Behnken Design (RSM-BBD) Optimization in transesterification of rice bran oil (RBO) to form biodiesel. The catalysts were characterized by Field Emission Scanning Electron Microscopy (FESEM), X-Ray powder Diffraction (XRD) and X-Ray Fluorescence analyses, its basic sites determined by back titration. The transesterification product, biodiesel was analyzed by Nuclear Magnetic Resonance (NMR) spectroscopy and RSM-BBD was also used to optimize the reaction variables on the biodiesel yield. The result reveals basic sites basic sites = 7.82mmol/g which is in close agreement with the experimental value of 7.38mmol/g. Also, quadratic model with high regression R2 = 0.9988 was obtained from the ANOVA of transesterification process, optimization at maximum biodiesel yield criterion give optimum transesterification conditions of catalyst loading=3.60 %(wt.), temperature = 65oC,time = 120 minutes, methanol molar ratio = 6 and response biodiesel yield = 89.20 %, also in close agreement with experimental value of 95.23 %. The amount of K in the optimized catalyst was only 2.26%and it was reused three times after initial use before its final deactivation